Interferon-γ release assay in HIV-infected patients with active tuberculosis: impact of antituberculous drugs on host immune response - Sauzullo, Ilaria; Mengoni, Fabio; Ermocida, Angela; Massetti, Anna P; D'Agostino, Claudia; Russo, Gianluca; Salotti, Alessandra; Falciano, Mario; Vullo, Vincenzo; Mastroianni, Claudio M (The New microbiologica, 2014)
The objective of the study was to: 1) investigate the performance of QuantiFERON-TB Gold In-Tube (QFT-GIT) in HIV-infected patients with active tuberculosis (TB); 2) evaluate the sequential changes in QFT-GIT assay during the treatment response; 3) investigate the direct in vitro effects of antituberculous drugs on both secretion of IFN-g and apoptosis of T cells. Forty-four HIV-patients with active TB were enrolled and tested with QFT-GIT. Thirteen of them were followed longitudinally by QFT-GIT, performed at baseline and six and nine months after TB-treatment onset. For in vitro experiments, cells from healthy donors and HIV-naive subjects were pretreated with four antituberculous-drugs, and then examined for IFN-g secretion and apoptosis of T-cells. The QFT-GIT was positive in 66%, negative in 11.3% and indeterminate in 22.7%. Longitudinal analysis in 13 HIV-TB subjects showed that at therapy completion a reversion to negative response was found only in 38.4% of patients, but in 30.7% the QFT-GIT remained positive. Overall, during the anti-TB treatment no significant decrease in average IFN-g response was observed in these patients (p<0.001). In vitro experiments showed that the four antituberculous- drugs, within the range of therapeutically achievable concentrations, did not exert any down-regulatory effect on IFN-g production and did not have any effect on apoptosis of T cells from HIV naïve subjects. Despite the high rate of indeterminate results, QFT-GIT assay may represent a good tool in the diagnostic workup for active TB in HIV-patients. Although the antituberculous drugs do not have any direct effect on host immune response to mycobacterial antigen, changes in longitudinal IGRA response have been found during in vivo anti-TB treatment.